ANALISIS SUBSISTEM AGRIBISNIS PADA USAHA SAYURAN HIDROPONIK BERBASIS NUTRIENT FILM TECHNIQUE (NFT) DI KOTA MEDAN STUDI KASUS PADA UMKM UDA SARAH - Hendra Saputra; Saniah Lidiya Hawani; Cris Diana Sidabutar; Heva Gracia Manurung; Joanna Brigitta; Aurel Ramadhanti Surya (Jurnal Agro Indragiri, 2026)
The development of urban agriculture through hydroponic technology is one solution toaddress land limitations and the increasing public demand for fresh and hygienic vegetables.This study aims to analyze the implementation of agribusiness subsystems in a hydroponicvegetable business based on Nutrient Film Technique (NFT) in Medan City with a case studyof the MSME "Uda Sarah". This study uses a qualitative approach with a case study design todeeply understand agribusiness management practices in micro-scale hydroponic businesses.Data collection was conducted through field observations, in-depth interviews with businessowners, documentation, and literature studies. Data analysis used the interactive analysismodel of Miles, Huberman, and Saldaña which includes data condensation, datapresentation, and drawing conclusions. The results show that the agribusiness system in theMSME "Uda Sarah" has been running through four main subsystems, namely the upstreamsubsystem, the farming subsystem (on-farm), the downstream or post-harvest subsystem,and the supporting service subsystem. The application of NFT technology supported byprecision nutrient management and a gradual planting system (rolling system) is able tomaintain production continuity and business efficiency. However, limited access to financing,business legality, and digital marketing optimization remain challenges in developinghydroponic businesses on a MSME scale in urban areas.